Bullying at school: how the use of music video discursive genre can prevent its spread (Research, Society and Development, 2023)
Law nº 13.663 of 05/14/2018 determines that the school instigates awareness measures against bullying, in order to promote a culture of peace for the formation of people and, thus, develop socio-emotional competence. Another point is that the school needs to discuss the topic so that the student can understand himself, the other and learn to respect the ethnic, cultural, social and religious pluralism of society. The objective of the research is to address the issues that guide violence at school, characterized mainly by the practice of bullying and its negative consequences for students. To carry out the research, a bibliographical survey was carried out with authors of national literature that deal with the subject in question, together with graphic material that explores the practice of the theme. The theoretical contributions came from the concepts of Gasparin, Kenski, Rojo, Bauman, Cerqueira Francisco, Mercado, Harari, Silva & Salles, Silva, among others. The results from this research indicated that there was an integrated work of readings, textual production, and digital literacy, as well as contributions from the sociocultural perspective, with regard to the theme of bullying.